2018
DOI: 10.1159/000490982
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Circular RNAs as a Novel Class of Putative Biomarkers for an Ocular Surface Disease

Abstract: Key WordsBackground/Aims: Pterygium is a common ocular surface disease with an unknown etiology and threatens vision as it invades into the cornea. Circular RNAs (circRNAs) are a novel class of RNA transcripts that participate in several physiological and pathological processes. However, the role of circRNAs in pathogenesis of pterygium remains largely unknown. Methods: G performed to identify pterygium -related circRNAs. GO analysis, pathway analysis, and miRNA response elements analysis was performed to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…CircRNAs may be secreted and circulate in body fluids, and their annular structure gives them strong resistance to RNA exonucleases or RNase R. Recent studies suggested that circRNAs could serve as good candidates for tumor biomarkers with high specificity and high sensitivity [ 58 , 59 ]. In gastric cancer (GC), hsa_circ_0001649 is downregulated in tumor tissue, consequently leading to lower expression in serum of GC patients after surgery, being a potential recurrence biomarker [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs may be secreted and circulate in body fluids, and their annular structure gives them strong resistance to RNA exonucleases or RNase R. Recent studies suggested that circRNAs could serve as good candidates for tumor biomarkers with high specificity and high sensitivity [ 58 , 59 ]. In gastric cancer (GC), hsa_circ_0001649 is downregulated in tumor tissue, consequently leading to lower expression in serum of GC patients after surgery, being a potential recurrence biomarker [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 669 circRNAs were found to be abnormally expressed in pterygium tissues (Li X.-M. et al, 2018). Further analysis revealed that the most enriched biological process and regulatory network of dysregulated circRNAs are the extracellular matrix organization and focal adhesion signaling pathways, respectively, which are highly correlated with the pathogenesis of pterygium (Li X.-M. et al, 2018).…”
Section: Ocular Surface Diseasesmentioning
confidence: 99%
“…In a recent study, 669 circRNAs were found to be abnormally expressed in pterygium tissues (Li X.-M. et al, 2018). Further analysis revealed that the most enriched biological process and regulatory network of dysregulated circRNAs are the extracellular matrix organization and focal adhesion signaling pathways, respectively, which are highly correlated with the pathogenesis of pterygium (Li X.-M. et al, 2018). The researchers focused on significantly upregulated circ_0085020 (circLAPTM4B) and found that its silencing weakened cellular viability, proliferation, and migration of pterygium fibroblasts and pterygium epithelial cells but increased UV-induced apoptosis (Li X.-M. et al, 2018).…”
Section: Ocular Surface Diseasesmentioning
confidence: 99%
“…Silencing promoted the proliferation and migration of pterygium fibroblasts and inhibited UV-induced apoptosis of pterygium epithelial cells. 132 Liu et al revealed that 101 circRNA species were differentially expressed in age-related cataract (ARC) lenses; there were 75 downregulated and 26 upregulated circRNA transcripts. CircHIPK3 is a highly conserved circRNA, and downregulation of circHIPK3 could lead to the overexpression of miR-193a, of which CRYAA is a target; CRYAA is a completely novel target gene of miR-193a in human lens epithelial cells (HLECs).…”
Section: Circrnas In Other Eye Diseasesmentioning
confidence: 99%
“…Circ_0085020 ( circ‐LAPTM4B ) was one of the substantially upregulated circRNAs in pterygium samples. Silencing promoted the proliferation and migration of pterygium fibroblasts and inhibited UV‐induced apoptosis of pterygium epithelial cells 132 . Liu et al revealed that 101 circRNA species were differentially expressed in age‐related cataract (ARC) lenses; there were 75 downregulated and 26 upregulated circRNA transcripts.…”
Section: Circrnas In the Retinamentioning
confidence: 99%